Almost home - Stewart, Mariah (Stewart, Mariah. Chesapeake diaries., 2011)
"When she was young, Steffie Wyler knew exactly what she wanted to do with her life: 1. Make ice cream. 2. Marry the coolest boy in town. 3. Live happily ever after. These days, Steffie is the proud owner of One Scoop or Two, a wildly popular ice cream parlor. Steffie's made a great life for herself in St. Dennis, but true love has never come knocking..."--Back cover.